Hubungan Antara Kualitas Informasi Program BIAS Sekolah Dasar Dengan Persepsi Orangtua Terhadap Vaksin - Rafika Hani; Sandy Permata (Prodi S1 Ilmu Komunikasi, Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Jakarta, 2025)
The utilization of renewable communication and information technology can facilitate organizations in disseminating information. This facility is utilized by SDIT Asy Syafi’i Jakarta Timur to provide information regarding the Program of Bulan Imunisasi Anak Sekolah (BIAS) for all parents through Official WhatsApp Group (KBM) application in every grade from the first to sixth class of Elementary School. The quality of information from the immunization program is expected to increase the vaccination rates in SDIT Asy Syafií. This research uses a quantitative method by spreading questionnaire survey for 111 respondents. This research purpose to find the influence of the relationship between the quality of information from the BIAS program in elementary schools and parents' perceptions of vaccines. The result of this research state there is a positive relationship between the quality of information and parents' perceptions. The correlation point is 0.627 and R Square point is 0,393. It indicates the influence of the independent variable of information quality to dependent variable of perception is 39,3%, meanwhile the rest value is 60,7% influenced by other factors outside of the x variable.